Soil Nutrient Characteristics After Rural Domestic Sewage Resource Utilization in Hilly Areas of Central Sichuan Province - Shan Li; Xinwen Ma; Yong Wu; Dongdong Gao; Jie Xiao (Shuitu baochi tongbao)
[Objective] The variation characteristics of various nutrient indexes in different types of soil in different soil layer after the application of harmless domestic sewage in the hilly area of central Sichuan Province were determined in order to provide scientific support for the harmless treatment and resource utilization of rural domestic sewage. [Methods] Rural domestic sewage treated by a three-grid septic tank was used for resource utilization. Three application treatments 〔G1(37.5 L/m2), G2(75 L/m2), and G3 (blank)〕 were applied to farmland; four application treatments 〔L1 (37.5 L/m2), L2 (75 L/m2), L3 (112.5 L/m2), and L0 (blank)〕 were applied to the forest land. The weight of each nutrient index was calculated by combining analytic hierarchy process (AHP) and principal component analysis (PCA), and the application effect of each scheme in different soil layers was comprehensively evaluated. [Results] ① Under the different resource utilization treatments of domestic sewage, except for L3, the soil nutrient evaluation grade was "good", and the domestic sewage utilization scheme was "excellent". ② Under each treatment, soil nutrient evaluation scores at different depths of farmland followed the order of G1 > G0 > G2. The scores for the 0—20 cm soil layer at forest land followed the order of L0 > L2 > L1 > L3. The scores for the 20—40 cm soil layer in forest land followed the order of L1 > L0 > L2 > L3. ③ Farmland has obvious effects on improving soil organic matter, total nitrogen, total phosphorus, available phosphorus, and available potassium. Under small application amounts, forest land had a better effect on increasing soil nutrients (other than available potassium) in the 20—40 cm layer. [Conclusion] In the short term, under the resource utilization of rural domestic sewage, an appropriate application amount could improve the nutrient status of farmland soil, and it could be better maintained for forest land without applying soil nutrients.